Respuesta :

Answer:

D

Step-by-step explanation:

[tex]x = (\frac{1}{3} \times 6) \div 9[/tex]

[tex]x = 2 \div 9[/tex]

[tex]x = \frac{2}{9} [/tex]

[tex]\bf \cfrac{9}{~~\frac{1}{3}~~}=\cfrac{6}{x}\implies \cfrac{\frac{9}{1}}{~~\frac{1}{3}~~}=\cfrac{6}{x}\implies \cfrac{9}{1}\cdot \cfrac{3}{1}=\cfrac{6}{x}\implies 27=\cfrac{6}{x}\implies 27x=6 \\\\\\ x=\cfrac{\stackrel{2}{~~\begin{matrix} 6 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}{\underset{9}{~~\begin{matrix} 27 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}\implies x = \cfrac{2}{9}[/tex]

ACCESS MORE